Analysis of the Role of the Agricultural Sector in the Economy in Batanghari District, Jambi Province, 2019 & 2021 - Masruroh, Khayatul; Putri, Faradilla Alisa; Rismawati, Rismawati; Osa, Afrilia; Fatimah, Nur; Hardianti, Khustiah; Rafidah, Rafidah; Hafiz, Ahsan Putra (International Journal of Economics (IJEC), 2024)
Economic growth is a macro indicator to see real economic performance in a region. The rate of economic growth can be calculated based on changes in GRDP at constant prices for the year in question compared to the previous year. Economic growth can be seen as an increase in the number of goods and services produced by all business fields of economic activity in a region during a year. This research aims to determine the leading agricultural sector in Batang Hari district, Jambi Province in the period 2019 and 2021 . This research uses quantitative research methods with Location Quotient (LQ) analysis which is used to determine leading and non-leading sectors using Statistical Location Quotient ( SLQ) and Dynamic Location Quotient (DLQ) to analyze calculations of ADHK GRDP in Batang Hari Regency.